1984
DOI: 10.1136/thx.39.1.52
|View full text |Cite
|
Sign up to set email alerts
|

Jaundice after open heart surgery: a prospective study.

Abstract: One hundred and fifty four consecutive adult patients having cardiac surgery for a variety of cardiac lesions were evaluated prospectively for postoperative jaundice, those with a raised preoperative serum bilirubin concentration (greater than 34 ,mol/I or 2 mg/100 ml) being excluded. The incidence of early postoperative jaundice, as defined by a serum bilirubin concentration of 50 ,umoUl (3.0 mg/100 ml) or greater, was 23*4%. The jaundice was mild (bilirubin concentration 51-100 ,umoll (3-.06.0 mg/100 ml)) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
68
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(72 citation statements)
references
References 21 publications
(5 reference statements)
4
68
0
Order By: Relevance
“…Nonsurvivors presented with significantly higher preoperative bilirubin levels. Patients with hepatic dysfunction, defined as the presence of preoperative jaundice associated with an elevated serum bilirubin above 3 mg/l, experienced a much higher mortality rate compared with the control group [23,24]. In patients with end-stage cardiac failure requiring ventricular assist device, a low preoperative bilirubin level has been shown to be the only significant predictor for survival [25].…”
Section: Discussionmentioning
confidence: 99%
“…Nonsurvivors presented with significantly higher preoperative bilirubin levels. Patients with hepatic dysfunction, defined as the presence of preoperative jaundice associated with an elevated serum bilirubin above 3 mg/l, experienced a much higher mortality rate compared with the control group [23,24]. In patients with end-stage cardiac failure requiring ventricular assist device, a low preoperative bilirubin level has been shown to be the only significant predictor for survival [25].…”
Section: Discussionmentioning
confidence: 99%
“…The decreased hepatic capacities for bilirubin disposal and bile transport, in addition to the haemolysis from CPB, cardiotomy suction, and mechanical prosthesis result in the postoperative hyperbilirubinemia. Both Weber [1] and Lockey [2] proposed that haemolysis contributed to postoperative jaundice; in contrast, Collins [3] and Chu [4] reported that serum TB concentration mainly resulted from increased CB, i.e., hepatic cellular jaundice. However, for the patients with postoperative hyperbilirubinemia in our study, 80.2% of the increased TB was due to an increase of both CB and UCB; 56.2% reached peak TB concentration on the first postoperative day, 33.5% on the second day and 10.3% on the seventh day.…”
Section: Discussionmentioning
confidence: 99%
“…The mortality can reach 85%-90% once the postoperative jaundice progresses to hepatic failure [4][5][6][7] . On the other hand, for patients with preoperative cirrhosis of liver, mortality of CPB surgery can reach 31% [8] .…”
Section: Discussionmentioning
confidence: 99%
“…One study reported that postoperative hyperbilirubinemia is associated with mortality, while others reported no association between elevated bilirubin and mortality [5]. Its incidence being associated with certain types of cardiac operations is another issue that has been considered.…”
Section: Introductionmentioning
confidence: 99%
“…Despite recent advances in surgical techniques and perioperative management, the incidence of postoperative hyperbilirubinemia after open-heart surgery is estimated to be nearly 20% [1,2,3,4,5,6,7,8,9,10], which has been consistent since the first report in 1967 [1,2]. Previous studies have suggested a number of possible risk factors underlying the development of postoperative hyperbilirubinemia, including age, heart failure [10,11], cardiopulmonary bypass time [9,10], transfusion [6,9], hemolysis [6] and sepsis [1].…”
Section: Introductionmentioning
confidence: 99%